Molecular determinants involved during Staphylococcus aureus colonization and/or infection - Askarian, Fatemeh (UiT The Arctic University of Norway, 2014)
Papers 1-3 of the thesis are not available in Munin: 1. Fatemeh Askarian, Maria Sangvik, Anne-Merethe Hanssen, Lars Snipen, Johanna U.E. Sollid and Mona Johannessen: ‘Staphylococcus aureus nasal isolates from healthy individuals cause highly variable host cell responses in vitro, The Tromsø Staph and Skin Study’, Pathogens and Disease, Volume 70, Issue 2, pages 158–166, March 2014, available at http://dx.doi.org/10.1111/2049-632X.12099 2. Fatemeh Askarian, Nina M. van Sorge, Maria Sangvik, Federico C. Beasley, Jorn R. Henriksen, Johanna U.E. Sollid, Jos A.G. van Strijp, Victor Nizet and Mona Johannessen: ‘A Staphylococcus aureus TIR Domain protein virulence factor blocks TLR2-mediated NF-κB signaling’, Journal of Innate Immunity, Vol. 6, No. 4, 2014, pages 485-498, available at http://dx.doi.org/10.1159/000357618 3. Fatemeh Askarian, Nina M. van Sorge, Anne-Merethe Hanssen, Diep Bao Dzung, Jos A.G. van Strijp, Johanna U. E. Sollid and Mona Johannessen: ‘Staphylococcus aureus SdrD promotes bacterial adherence to keratinocytes and whole blood survival’, manuscript. Given the link between the compelling impact of Staphylococcus aureus colonization on the risk and outcome of infection, strategies to prevent nasal colonization could be an appealing method of fighting infection. The ability of S. aureus to colonize and infect a host is a balance between its multitudes of virulence factors and the host immune defence mechanisms. Despite the multiple bacterial factors known to be associated with colonization, little is known about the relative contribution of the host determinants. This study explores selected molecular determinants associated with colonization and/or infection, to present a new insight on S. aureus interactions with the human host. In theory, the breakage of the interaction between host and S. aureus may open new avenues for developing novel therapeutic strategies. However, pursuit of such golden goal merits further investigations.